Pengaruh Penggunaan Model Guided Inquiry Terhadap Keterampilan Menulis Teks Eksposisi pada Siswa Kelas VIII SMP Taruna Sakti Pekanbaru - Zelvia Salsabila; M. Nur Mustafa; Oki Rasdana (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the effect of using the guided inquiry learning model on the expository writing skills of eighth-grade students at SMP Taruna Sakti Pekanbaru. The study employed a quantitative approach using a pre-experimental method through a One-Group Pretest-Posttest Design. The study population consisted of 46 eighth-grade students at SMP Taruna Sakti Pekanbaru. The research sample was determined using purposive sampling, resulting in one class of 23 students serving as the experimental group, which was taught using the guided inquiry learning model. Data collection was conducted through expository writing tests in the form of pretests and posttests. The data were analyzed using the nonparametric Wilcoxon Signed Rank Test because the data were not normally distributed. The results showed a significant difference between the pretest and posttest learning outcomes of the experimental class, with a significance level of 0.001 < 0.05. The students’ average pretest score was 69.043, which increased to 81.521 on the posttest. These findings indicate that the implementation of the guided inquiry learning model has a significant effect on improving students’ expository writing skills because it encourages active engagement, critical thinking, and the ability to develop ideas systematically.